Strain-induced N–N bonding and magnetic changes in monolayer intrinsic ferromagnetic TmN2 (Tm = Tc and Nb). (30th May 2019) - Li, Ruixin; Yang, Baishun; Li, Fangfang; Wang, Yanjie; Du, Xiaobo; Yan, Yu
Abstract: The modulation of magnetic property in two-dimensional (2D) intrinsic ferromagnets is important for their future application in spintronic devices at the nanoscale. In this work, using first-principles calculation, we investigate the effects of strain on the structures, electronic structures and magnetic properties of monolayer 1H-NbN2 and 1H-TcN2 . The results show that both the unstrained monolayer 1H-NbN2 and 1H-TcN2 are 2D intrinsically ferromagnetic (FM) metal, in which the magnetic moment of the 1H-NbN2 and 1H-TcN2 comes mainly from the d orbitals of Nb atom and the p orbitals of N atom, respectively. Remarkably, two neighboring N atoms in the unstrained 1H-NbN2 form N–N bond, while those in the 1H-TcN2 do not. When lattice constant a increases to 3.17 Å, monolayer 1H-TcN2 undergoes N–N nonbonding-bonding transition at which the distance between the N atoms d N–N suddenly drops by almost 25%. In particular, due to the bonding between two neighboring N atoms, the magnetic moment of N atoms in 1H-TcN2 are quenched and the ground state transfers to non-magnetic. In contrast, when a decreases to 3.18 Å, monolayer 1H-NbN2 undergoes N  −  N bonding-nonbonding transition at which the d N–N suddenly increases from 1.79 Å to 1.97 Å. The N–N bonding-nonbonding transition induces the magnetic moments to transfer from the d orbitals of Nb atom to the p orbitals of N atom, while ground state of monolayer 1H-NbN2 remains FM metal.